PERANCANGAN PROTOTIP PERANGKAT LUNAK PENERIMAAN DAN PENELUSURAN ORDER DI INDUSTRI GARMEN. - agus alim (Entrepreneurship Faculty, Universitas Garut, 2019)
Industrial Revolution 4.0 era made indutries is more competitifeness. Information Technology is must be used to be successfull. Marketing division of industries as a vital part of the organization needs software as as tool for data entry and tracking order on the garment industry. There are parameters in this software i.e.: Buyer Lead Time, Monthly Target Configuration, Maintenance Data and Configuration Setting (user, division, team and buyer). The Data Output from this simulation are Performance Scorecard, Tracking Report, and provide features color arrangement to give an indication tool for management to take actions when it needs. Based on the testing result, this design prototype has been full fill the content ( Entry Data and Tracking Order System on Garment Industry) criteria and also programming technology side i.e., program code, so these media can be used as a learning media.